Review of Perioperative Music Medicine: Mechanisms of Pain and Stress Reduction Around Surgery - Ginsberg, J. P.; Raghunathan, Karthik; Bassi, Gabriel; Ulloa, Luis (Frontiers in Medicine, 2022)
Clinical-experimental considerations and an approach to understanding the autonomic basis of improved surgical outcomes using Perioperative Music Medicine (PMM) are reviewed. Combined surgical, psycho-physiological, and experimental perspectives on Music Medicine (MM) and its relationship to autonomic nervous system (ANS) function are discussed. Considerations are given to the inter-related perioperative effects of MM, ANS and pain, and underlying vagal and other neural circuits involved in emotion regulation and dysregulation. Many surgical procedures are associated with significant pain, which is routinely treated with post-operative opioid medications and which bring an additional set of detrimental side effects and delay recovery. Surgical trauma shifts the sympathetic autonomic nervous system to a sustained activation impairing physiological homeostasis and causing psychological stress, as well as metabolic and immune dysfunction that contribute to postoperative mortality and morbidity. In this article we propose a plan to operationalize the study of mechanisms mediating the effects of MM in perioperative settings of orthopedic surgery (total knee replacement). Using a parallel experimental rodent model of orthopedic surgery, we also propose to test the neuronal networks that we hypothesize mediate music modulation of peripheral- and psycho-physiology feedback control of homeostasis and affect emotion regulation.